(untitled) (Research, Society and Development, 2021)
Among the prevention tools in the context of public health, vaccination deserves to be highlighted. Recently, however, immunizations have come to face major obstacles in the national territory, with the increase in the rates of certain infectious diseases and the heterogeneity of vaccination coverage in different Brazilian regions. Thus, this study aims to know the coverage of vaccines recommended by the Ministry of Health for adolescents, adults and the elderly, in the municipality of Marabá, in the period from 2015 to 2020. It is an observational, cross-sectional and descriptive study, where they were interviewed vaccination rooms of the UBS (Basic Health Unit) in the urban area of Marabá. The data were collected through a questionnaire previously prepared by the researchers and through information from the Department of Informatics of the Unified Health System (DATASUS). The research offered risks regarding the loss of confidentiality of information and embarrassment on the part of the interviewees and the transmission and illness of the new coronavirus. The results showed an average vaccination coverage of 57.49% in the period and place evaluated; there was an absence of data on the coverage of vaccines against influenza and HPV; girls were vaccinated more than boys against HPV, according to doses applied; the lack of knowledge about the importance of vaccination was the main reason for this public’s non-adherence to vaccination, according to professionals in the vaccination rooms. Comparative studies corroborated the hypotheses and supported expansion strategies listed by such employees and highlighted low percentages of vaccination coverage in several Brazilian locations. The need to intensify vaccination campaigns is undeniable, in order to provide greater attraction and awareness of the target audience.